An integrated approach with homeopathic medicine and electro-acupuncture in anaesthesiology during breast cancer surgery: Case reports - Bosco F; Cidin S; Maceri F; Ghilli M; Roncella M; De Simone L (Korean Pharmacopuncture Institute, 2018)
This study investigates the effect of a combination of homeopathic medicine and electro- acupuncture in two patients with breast cancer and severe liver disease who could not receive standard anaesthesia therapy due to liver problems. Specifically, measurable and quantifiable parameters were used to evaluate whether an integrated approach-consisting of electro- acupuncture and a homeopathic medicine diluted above Avogadro's limit (that is, above a potency of 12CH) during the pre-surgical, surgical and post-surgical phases-can improve general well-being of a patient undergoing breast cancer surgery. In breast cancer surgery, we employed an integrated approach consisting of induction with hypnotics and muscle relaxants, followed by maintenance with anaesthetic gas, combined with a homeopathic treatment (Arnica montana 15CH and Apis mellifica 15CH) before and after surgery and an electro- acupuncture treatment performed in the preand post-surgical phases without any analgesic/pain relieving medications. Both of the patients treated with the integrated approach improved their overall condition without need for other common pain relieving medicines. Additionally, thanks to their rapid awakening, the patients were not relocated to a protected area and the hospitalization was shorter. A multidisciplinary approach incorporating homeopathic medicine and electro-acupuncture can be a solution for patients who need or ask about a different and/or safer alternative to the standard treatment. This approach can offer a safe, much less expensive, non-invasive and viable alternative for such cases. Moreover it can be useful for an opioids free anesthesia.